Optimizing Aerobic Capacity Through Long Interval Training Based on High Maximum Aerobic Speed - Irgi Apprilla Hizkia Rifa Putri; Dikdik Zafar Sidik; Fitri Rosdiana (Journal of Physical Education Health and Sport, 2025)
This study aims to examine the effectiveness of the Long Interval Training (LIT) method adapted to high Maximum Aerobic Speed (MAS) capacity on increasing aerobic capacity. Aerobic capacity is the body’s ability to absorb and use oxygen during exercise and is closely related to VO₂max. This capacity is important for physical performance, especially in middle and long distance races. This study used an experimental method with a One Group Pretest-Posttest design through purposive sampling. The treatment was given for 16 training sessions, and the measurement test was carried out with the Balke Test before and after treatment (pre-test and posttest). Data were analyzed using Data Descriptive Analysis, Shapiro-Wilk normality test, and Paired Samples t-Test test. The results showed a significant increase in VO₂max value after treatment. The Paired Samples t-Test test shows a significance value (Sig. 2-tailed) of 0.018, which is smaller than 0.05, so there is a significant difference between the pre-test and post-test scores. This proves that the high MAS-based LIT method is effective in increasing aerobic capacity. This study emphasizes the importance of good training load management, close supervision, and proper recovery strategies. Therefore, although the LIT method was shown to be effective, safe and sustainable implementation should consider the athlete’s overall training load to prevent injury and fatigue.